2002
DOI: 10.1007/s007020200055
|View full text |Cite
|
Sign up to set email alerts
|

The neuromelanin of human substantia nigra and its interaction with metals

Abstract: Neuromelanin (NM) is a peculiar biochemical component of several neurons in the Substantia Nigra (SN), the target area of the degenerative process in Parkinson Disease (PD). SN NM has peculiarities as to its composition and an impressive capacity of chelating metals, iron in particular, but not exclusively. Gaining insights into the structural and functional characteristics of NM should help understanding the reasons of selective vulnerability of nigral neurons in many parkinsonian conditions. From the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 43 publications
1
57
0
4
Order By: Relevance
“…In the SN of PD patients, redox-active iron levels are increased by 30 -35% compared with age-matched controls (for review, see Zecca et al, 2004;Götz et al, 2004). Neuromelanin, a dark pigment produced in catecholaminergic neurons of the human SN and locus ceruleus, acts as a storage system for iron in dopaminergic neurons (Zecca et al, 2002) and has been found to associate with large amounts of iron in diseased nigral tissue (Jellinger et al, 1992(Jellinger et al, , 1993. Neuromelanin could potentially serve a neuroprotective function by sequestering free intracellular iron.…”
Section: Resultsmentioning
confidence: 99%
“…In the SN of PD patients, redox-active iron levels are increased by 30 -35% compared with age-matched controls (for review, see Zecca et al, 2004;Götz et al, 2004). Neuromelanin, a dark pigment produced in catecholaminergic neurons of the human SN and locus ceruleus, acts as a storage system for iron in dopaminergic neurons (Zecca et al, 2002) and has been found to associate with large amounts of iron in diseased nigral tissue (Jellinger et al, 1992(Jellinger et al, , 1993. Neuromelanin could potentially serve a neuroprotective function by sequestering free intracellular iron.…”
Section: Resultsmentioning
confidence: 99%
“…[84] Neuromelanin has been reported to have a dichotomous role (adverse or protective): beneficial when it reduces the oxidative stress in the brain due to its ability to bind cations; detrimental when it exacerbates the oxidative stress releasing H 2 O 2 or by reducing redox-active metals to a more reactive state. [85][86][87] Particular efforts have been made in understanding the binding of iron to neuromelanin, [76,[88][89][90][91][92][93][94][95] as iron was reported in dopaminergic neurons of Parkinsonian brains. [8] Recently, Sepia melanin has been identified as a suitable model to describe the binding characteristics of neuromelanin.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies mainly concerned the ability of neuromelanin to bind iron, which may determine the risk of oxidative stress in the Substantia nigra and Locus coeruleus of the human brain (Kropf et al, 1998;Shima et al, 1997;Zecca et al, 2001Zecca et al, , 2002 or ion-exchange properties of Sepia melanin, which is probably not a very good model for human eumelanin Liu et al, 2004;Samokhvalov et al, 2004).…”
Section: Ion-exchange Propertiesmentioning
confidence: 99%